Insights into the role of thrombin in the pathogenesis of recurrent ischaemia after acute coronary syndrome - Weitz, Jeffrey I. (Thrombosis and Haemostasis, 2014)
Acute coronary syndrome (ACS) is a medical emergency. Patients who survive the initial event remain at risk of recurrent cardiovascular events. In most cases, ACS is triggered by thrombosis after rupture of an atherosclerotic plaque. Key to thrombus formation at this site is the generation of thrombin, which not only converts fibrinogen to fibrin but also serves as a potent platelet agonist and induces platelet aggregation at the site of vascular injury. Although dual antiplatelet therapy is more effective for the prevention of recurrent events than aspirin alone after ACS, there remains an approximately 10 % risk of recurrent ischaemic events at one year. Recent studies have evaluated whether the addition of an anticoagulant to antiplatelet therapy reduces the risk of recurrent ischaemia after an ACS event. Rivaroxaban, an oral factor Xa inhibitor, attenuates thrombin generation. When used in conjunction with dual antiplatelet therapy in patients with stabilised ACS, rivaroxaban 2.5 mg twice daily significantly reduced the risk of the composite endpoint of cardiovascular death, myocardial infarction and stroke compared with placebo. Although it increased the risk of bleeding, rivaroxaban was associated with a reduction in mortality; a finding that supports the use of a dual-pathway approach that combines anticoagulant and antiplatelet therapy. This review explores the pathophysiology of ACS to provide perspective on the results of recent clinical trials with novel oral anticoagulants for ACS and to identify their potential role in this setting.
Keywords: Acute coronary syndrome; thrombin; thrombosis; factor Xa; rivaroxaban